The return [large type] - Fisher, Suzanne Woods (Fisher, Suzanne Woods. Amish beginnings novel, 2017)
Beautiful and winsome, Betsy Zook never questioned her family's rigid expectations, nor those of devoted Hans, but then she never had to. Not until the night when she's taken captive in a surprise Indian raid. During her captivity, Betsy faces brutality and hardship, but also unexpected kindness. She draws strength from native Caleb, who encourages her to find God in all circumstances. She finds herself torn between her pious upbringing and the intense new feelings this compelling man awakens within her. Handsome and complex, Hans is greatly anguished by Betsy's captivity and turns to Tessa Bauer for comfort. Eagerly, Tessa responds, overlooking troubling signs of Hans's hunger for revenge. When Betsy is finally restored to the Amish, have things gone too far between Hans and Tessa?